2013
DOI: 10.1016/j.pdpdt.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photofrin-mediated photocytotoxicity on a panel of human pancreatic cancer cells

Abstract: Summary Background and objective Pancreatic cancer is a leading cause of cancer-related deaths in men and women. Early clinical studies suggest that photodynamic therapy (PDT) might be a useful modality in the management of this deadly disease. In this study, the photocytotoxicity of Photofrin-mediated PDT on different human pancreatic cancer cells (BxPc-3, HPAF-II, Mia PaCa-2, MPanc-96, PANC-1 and PL-45) was examined. Materials and methods After co-incubating cancer cells with Photofrin (0—10 [H9262]g/ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…As our findings in this study were based on in vitro cell culture observations with microscopy, it is still difficult to compare the PDT efficacy of XL147 with those of currently available photosensitizers for clinical PDT. However, earlier studies reported that Photofrin, which is one of the most frequently used PDT photosensitizers in oncology, induced apoptosis in carcinoma cell lines including PC3 cells by ∼6 J/cm 2 , similar to the light dose we used in this study . In addition, evidence has been provided for the clinical benefit of XL147 in patients with advanced solid tumors, lymphoma, and chronic lymphocytic leukemia by its pharmacological impact on class I PI3Ks .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As our findings in this study were based on in vitro cell culture observations with microscopy, it is still difficult to compare the PDT efficacy of XL147 with those of currently available photosensitizers for clinical PDT. However, earlier studies reported that Photofrin, which is one of the most frequently used PDT photosensitizers in oncology, induced apoptosis in carcinoma cell lines including PC3 cells by ∼6 J/cm 2 , similar to the light dose we used in this study . In addition, evidence has been provided for the clinical benefit of XL147 in patients with advanced solid tumors, lymphoma, and chronic lymphocytic leukemia by its pharmacological impact on class I PI3Ks .…”
Section: Discussionsupporting
confidence: 70%
“…However, earlier studies reported that Photofrin, which is one of the most frequently used PDT photosensitizers in oncology, induced apoptosis in carcinoma cell lines including PC3 cells by 6 J/cm 2 , similar to the light dose we used in this study. 41,42 In addition, evidence has been provided for the clinical benefit of XL147 in patients with advanced solid tumors, lymphoma, and chronic lymphocytic leukemia by its pharmacological impact on class I PI3Ks. 22,43 Therefore, we can say that XL147 is a drug that is expected to have both antitumor effects of a PI3K inhibitor and a photosensitizer when illuminated by blue light.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 99%
“…In our previous study, we demonstrated that DHA induces apoptosis by up-regulating the expression of Bax, down-regulating Bcl-2, Bcl-xL and procaspase-3 and increasing caspase-9 activation and induced cell cycle arrest by down-regulating cyclin E, CDK2 and CDK4 [17]. Furthermore, PDT induces apoptosis in esophageal cancer cells [5], hepatic cancer cells [26], pancreatic cancer cells [27] as well as the human head and neck cancer cells AMC-HN-4 [28]. Similarly, in the present study, we found that 5-ALA-PDT induced apoptosis in esophageal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are some preclinical studies about the maintained organs' tumor. PDT with Pcs and PS of pancreatic cancer and colon tumor studies show that the results are encouraging toward future clinical applications of PDT for pancreatic cancer and colon tumor in literature (26)(27)(28)(29)(30)(31). Tzerkovsky et al (32) firstly reported on feasibility of efficient use of PDT with a PS of chlorin series and AAT with bevacizumab for the treatment of brain tumors in experimental models.…”
Section: Radiolabeling Resultsmentioning
confidence: 98%